Human papillomavirus prevalence in invasive laryngeal cancer in the United States. - Brenda Y Hernandez; Marc T Goodman; Charles F Lynch; Wendy Cozen; Elizabeth R Unger; Martin Steinau; Trevor Thompson; Maria Sibug Saber; Sean F Altekruse; Christopher Lyu; Mona Saraiya; HPV Typing of Cancer Workgroup (PLoS ONE)
Purpose Human papillomavirus (HPV) is a major risk factor for specific cancers of the head and neck, particularly malignancies of the tonsil and base of the tongue. However, the role of HPV in the development of laryngeal cancer has not been definitively established. We conducted a population-based, cancer registry study to evaluate and characterize the genotype-specific prevalence of HPV in invasive laryngeal cancer cases diagnosed in the U.S. Methods The presence of genotype-specific HPV DNA was evaluated using the Linear Array HPV Genotyping Test and the INNO-LiPA HPV Genotyping Assay in formalin-fixed paraffin embedded tissue from 148 invasive laryngeal cancer cases diagnosed in 1993-2004 within the catchment area of three U.S. SEER cancer registries. Results HPV DNA was detected in 31 of 148 (21%) invasive laryngeal cancers. Thirteen different genotypes were detected. Overall, HPV 16 and HPV 33 were the most commonly detected types. HPV was detected in 33% (9/27) of women compared with 18% (22/121) of men (p = 0.08). After adjustment for age and year of diagnosis, female patients were more likely to have HPV-positive laryngeal tumors compared to males (adjusted OR 2.84, 95% CI 1.07-7.51). Viral genotype differences were also observed between the sexes. While HPV 16 and 18 constituted half of HPV-positive cases occurring in men, among women, only 1 was HPV 16 positive and none were positive for HPV 18. Overall 5-year survival did not vary by HPV status. Conclusions HPV may be involved in the development of a subset of laryngeal cancers and its role may be more predominant in women compared to men.